The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1117/1.2830658
|View full text |Cite
|
Sign up to set email alerts
|

In vivo time-resolved autofluorescence measurements to test for glycation of human skin

Abstract: This paper presents an evaluation of time-resolved fluorescence measurements on human skin for screening type 2 diabetes. In-vivo human skin was excited with a pulse diode at 375 nm and pulse width of 700 ps. Fluorescence decays were recorded at four different emission wavelengths 442, 460, 478 and 496 nm. Experiments were performed on various locations including the palms, arms, legs, and cheeks of a healthy Caucasian subject to test single-subject variability. The fluorescence decays obtained were modeled us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…An interesting feature of fluorescence (and Raman spectroscopy, see Section 3.2.10) is that these measurements can be performed in a noninvasive manner. For example, the AGE-related fluorescence of skin and the eye lens have been measured [132][133][134][135][136]. Interestingly, AGE-related fluorescence of the human skin has been correlated with vascular complications [137], renal function [132,138,139], diabetes [140], obesity [141], and even mental disorders [142].…”
Section: Fluorescence Spectrometrymentioning
confidence: 99%
“…An interesting feature of fluorescence (and Raman spectroscopy, see Section 3.2.10) is that these measurements can be performed in a noninvasive manner. For example, the AGE-related fluorescence of skin and the eye lens have been measured [132][133][134][135][136]. Interestingly, AGE-related fluorescence of the human skin has been correlated with vascular complications [137], renal function [132,138,139], diabetes [140], obesity [141], and even mental disorders [142].…”
Section: Fluorescence Spectrometrymentioning
confidence: 99%
“…In addition, Rajaram et al studied non-melanoma skin cancer in vivo using a combination of diffuse reflectance and fluorescence spectroscopy [33], while Blackwell et al used an instrument recording fluorescence decays in four spectral channels to compare the fluorescence signature of human skin from diabetic and non-diabetic test subjects in vivo [44].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few reports on the applicability of FLM to examination of AGEs in vivo. For example, Blackwell et al used FLM on the human skin for diagnosis of diabetes, and showed non-significant difference between the fluorescence lifetimes of nondiabetic and diabetic subjects [21]. Thus, the relationship between fluorescence lifetime and degree of glycation remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%